2014
DOI: 10.1007/bf03379613
|View full text |Cite
|
Sign up to set email alerts
|

Telomeres in the Brain Cortex of Patients with Major Depressive Disorder

Abstract: Telomeres are complex structures formed by the end of the DNA molecule at the tip of each chromosomal arm. The repeated (TTAGGG) telomeric sequence progressively shortens during lifespan because it cannot be replicated as somatic cells divide, and is highly susceptible to breakage by free radicals. Critically shortened telomeres activate the genetic program of cell senescence and/or apoptosis. The telomere length measured in peripheral blood leucocytes is considered a reliable marker of biological age, mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Our results add support to the notion of increased involvement of the visual cortices when attention is directed to the emotional valence of the stimuli (Dima et al, 2011;Gregoriou, Gotts, Zhou, & Desimone, 2009). Similarly, in brain tissue, no decrease in TL has been observed in studies quantifying telomere length in the occipital cortex (Teyssier, Ragot, Donzel, & Chauvet-Gelinier, 2010) of subjects with psychiatric disorders and Holstege et al (2014) showed that there is a differential effect of aging on brain tissues taken from the same individual, where the occipital cortex has the longest telomeres compared with all other brain areas. However, recently equal attention has been drawn to the occipital lobe and its coupling to the VPFC as it seems that this coupling is a critical component of the brain network processing faces (Dima et al, 2011;Pessoa & Adolphs, 2010;Piech et al, 2010;Tsuchiya, Moradi, Felsen, Yamazaki, & Adolphs, 2009).…”
Section: The Effect Of Tl On the Facial Affect-processing Networksupporting
confidence: 86%
See 1 more Smart Citation
“…Our results add support to the notion of increased involvement of the visual cortices when attention is directed to the emotional valence of the stimuli (Dima et al, 2011;Gregoriou, Gotts, Zhou, & Desimone, 2009). Similarly, in brain tissue, no decrease in TL has been observed in studies quantifying telomere length in the occipital cortex (Teyssier, Ragot, Donzel, & Chauvet-Gelinier, 2010) of subjects with psychiatric disorders and Holstege et al (2014) showed that there is a differential effect of aging on brain tissues taken from the same individual, where the occipital cortex has the longest telomeres compared with all other brain areas. However, recently equal attention has been drawn to the occipital lobe and its coupling to the VPFC as it seems that this coupling is a critical component of the brain network processing faces (Dima et al, 2011;Pessoa & Adolphs, 2010;Piech et al, 2010;Tsuchiya, Moradi, Felsen, Yamazaki, & Adolphs, 2009).…”
Section: The Effect Of Tl On the Facial Affect-processing Networksupporting
confidence: 86%
“…The finding that increased cuneus activation is associated with longer TL is one which is complemented by our connectivity results that showed that the facial affect information forwarded from the IOG to the VPFC is significantly increased with longer TLs. Similarly, in brain tissue, no decrease in TL has been observed in studies quantifying telomere length in the occipital cortex (Teyssier, Ragot, Donzel, & Chauvet-Gelinier, 2010) of subjects with psychiatric disorders and Holstege et al (2014) showed that there is a differential effect of aging on brain tissues taken from the same individual, where the occipital cortex has the longest telomeres compared with all other brain areas. Our results contribute to this discussion by highlighting a potential role of TL in the occipital lobe, and by supplementing the current belief that TL in the occipital lobe is less susceptible to the effects of age and disease, while playing a role in emotional processing.…”
Section: The Effect Of Tl On the Facial Affect-processing Networkmentioning
confidence: 95%
“…Recent studies demonstrate shortened telomeres in leukocytes of MDD patients, and also in subjects exposed to extended periods of psychological stress (Hoen et al, 2011;Wolkowitz et al, 2011a;Garcia-Rizo et al, 2013;Puterman et al, 2013). However, telomere shortening was not observed previously in post-mortem brain tissues from MDD (Teyssier et al, 2010;Zhang et al, 2010). These past brain findings have been used to reason that brain cells may not be susceptible to the same factors that contribute to telomere shortening in leukocytes.…”
Section: Discussionmentioning
confidence: 82%
“…For example, accelerated telomere shortening as a result of life stresses could contribute to loss of susceptible cells in the brain, an intriguing possibility because numerous researchers have reported reduced numbers of cells in post-mortem brains from MDD subjects (Ongür et al, 1998;Duman et al, 2000;Rajkowska, 2000;Rajkowska and Miguel-Hidalgo, 2007). However, to our knowledge there are only two studies that have examined telomere lengths in post-mortem brain tissues from individuals with stress-related psychiatric disorders (Teyssier et al, 2010;Zhang et al, 2010). In both of these studies, telomere lengths were similar in psychiatric disorders including MDD and normal control subjects, suggesting that telomere shortening in MDD does not negatively impact cellular health of the brain.…”
Section: Introductionmentioning
confidence: 92%
“…10 There is clearly much to learn in this regard, as lithium therapy has not been shown to modulate leukocyte telomerase function. colleagues 12 reported no difference between patients with depression and healthy controls. On the other hand, Sequeira and colleagues 13 found telomere shortening in the hippo cam pi, but not the dorsolateral prefrontal cortex, of indi viduals with depression.…”
Section: On Telomeres Long and Shortmentioning
confidence: 96%